FORMATION PROCESS OF COASTAL ECOREGIONS IN RELATION TO QUATERNARY GEOLOGICAL ACTIVITIES IN BINH THUAN PROVINCE - Xuyen, Duong Thi Thanh; Tuan, Nguyen Van; Nghi, Tran; Thai, Nguyen Dinh; Tuyen, Nguyen Thi (Vietnam Journal of Marine Science and Technology, 2017)
Endogenous and exogenous geological processes have divided the coastal zone of Binh Thuan province into four typical ecological zones: Late-Holocene plain ecoregion with river-marine origin which is distributed between coastal sand dunes and the foot/base of the Truong Son mountains, coastal sand dune ecoregion 0 - 150 m high, tidal ecoregion 0 - 5 m deep, bottom-sediment ecoregion 5 - 25 m deep and the ancient shoreline ecoregion 25 - 30 m deep. The plain ecoregion and the subterranean bays were formed mainly due to the subsidence motion and the sedimentation in relation to the sea level change in the Holocene. The sand dune ecoregion was the result of the evolution process of five sand formation cycles in relation to five cycles of sea level change in the Quaternary due to the effects of five glacial cycles and interglacier Gunz/GM, Mindel/MR, Riss/R-W1, Wurm/W1-W2 and Wurm2/Flandrian transgression